Development of E-Module Assisted by Book Creator in Indonesian Language for Third-Grade Students at SDN 01 Sitiung - Martiya Nurni Khairita; Amar Salahuddin; Olga Pratiwi (The Future of Education Journal, 2025)
This research is motivated by the lack of student interest in reading materials presented conventionally through textbooks. Text materials are often considered boring by students due to the lack of presentation variation and minimal supporting illustrations that are engaging. As a result, students tend to be passive during lessons and struggle to comprehend the content of the reading and construct sentences that match the context of the theme. The solution is to develop an E-Module Assisted by Book Creator in the Indonesian Language subject for third-grade students at SDN 01 Sitiung that is valid, practical, and effective. This research is a Research and Development study using the ADDIE development model, which includes several stages: Analyze, Design, Development, Implementation, and Evaluation. The assessment instruments were evaluated by three validators: content validator, language validator, and graphic design validator. The instrument sheets were filled out using validation sheets for the validators and practicality sheets evaluated by practitioners. The results of the development of the E-Module Assisted by Book Creator in the Indonesian Language subject for third-grade students at SDN 01 Sitiung show that the validators gave an average score of 85.48%, categorized as highly valid. The practicality score averaged 94.2%, categorized as very practical, and the effectiveness score averaged 87.4%, categorized as very effective.